Analysis of Mortality from Asbestos-Related Diseases in Brazil Using Multiple Health Information Systems, 1996-2017 - Eduardo Algranti; Vilma S. Santana; Felipe Campos; Leonardo Salvi; Cézar A. Saito; Franciana Cavalcante; Heleno R. Correa-Filho (Elsevier, 2022)
Background: In Brazil, asbestos was intensively used from the 1960s until its ban in 2017. Mesothelioma, asbestosis, and pleural plaques are typical asbestos-related diseases (ARD-T). To create an ARD-T national database, death records from 1996-2017 were retrieved from several health information systems (HIS). Methods: All national HIS containing coded diagnoses (ICD-10) and death information were obtained. Linkage was performed to create a single database of ARD-T death records, either as underlying or contributory causes, in adults aged 30 years and older. Results: A total of 3,057 ARD-T death records were found, 2,405 (76.4%) of which being malignant mesotheliomas (MM). Pleural MM (n = 1,006; 41.8%) and unspecified MM (n = 792; 32.9%) prevailed. Male to female MM ratio (M:F) was 1.4:1, and higher ratios were found for non-malignant ARD-T: 3.5:1 for asbestosis and 2.4:1 for pleural plaques. Male crude annual mesothelioma mortality (CMmm x1,000,000) was 0.98 in 1996 and 2.26 in 2017, a 131.1% increment, while for females it was 1.04 and 1.25, a 20.2% increase, correspondingly. The small number of deaths with asbestosis and pleural plaques records precluded conclusive interpretations. Conclusions: Even with the linkage of several HIS, ARD-T in death records remained in low numbers. MM mortality in men was higher and showed a rapid increase and, along with non-malignant ARD-T, higher M:F ratios suggested a predominant pattern of work-related exposure. The monitoring of workplace and environmental asbestos exposure needs to be improved, as well as the workers surveillance, following the recent Brazilian ban.